European multicentre study to define disease activity criteria for systemic sclerosis. I. Clinical and epidemiological features of 290 patients from 19 centres. Issue 6 (1st June 2001) - Della Rossa, A; Valentini, G; Bombardieri, S; Bencivelli, W; Silman, A J; D'Angelo, S; Cerinic, M Matucci; Belch, J F; Black, C M; Becvar, R; Bruhlman, P; Cozzi, F; et al.
Abstract : OBJECTIVE: To investigate the existence of differences among European referral centres for systemic sclerosis (SSc) in the pattern of attendance and referral and in the clinical and therapeutical approaches. METHODS: In 1995 the European Scleroderma Study Group initiated a multicentre prospective one year study whose aim was to define the disease activity criteria in SSc. During the study period each participating European centre was asked to enrol consecutive patients satisfying American College of Rheumatology criteria for SSc and to fill out for each of them a standardised clinical chart. Patients from various centres were compared and differences in epidemiological, clinical, and therapeutical aspects were analysed. RESULTS: Nineteen different medical research centres consecutively recruited 290 patients. The patients could be divided into two subgroups: 173 with the limited (lSSc) and 117 with the diffuse (dSSc) form of the disease. The clinical and serological findings for the series of 290 patients seemed to be similar to data previously reported. However, when the data were analysed to elicit any differences between the participating centres, a high degree of variability emerged, in both epidemiological and clinical features and in the diagnostic and therapeutic approaches to the disease. CONCLUSIONS: The clinical approach to SSc, not only in different countries but also in different centres within the same country, is not yet standardised. To overcome this problem, it will be necessary for the scientific community to draw up a standardised procedure for the management of patients with SSc. This would provide a common research tool for different centres engaged in research on this complex disease.